International integration: past and present: study aid - Ragozin D. V. Dmitrii Valerievich (Tomsk, Tomsk Polytechnic University Publishing House, 2016)
This study aid provides basic information on international integration, its patterns, and main approaches to its research analyzing the most important global and regional international organizations. The study aid has been based on the original Russian- and English-language materials and is fully coasistent with the course of "International integration and international organizations".